Problems of ensuring the rights of the suspect during the pre-trial investigation (Journal of actual problems of jurisprudence, 2023)
The article deals with the problems of ensuring the rights of a suspect during the pre-trial investigation. The issues of balancing the interests of the individual and the state, which are most clearly manifested in the criminal process, are actualized by the example of the realization of the rights of the suspect, as well as the need for further improvement of legislation defining the legal regime of personal inviolability in criminal proceedings. The legal analysis of guarantees of ensuring the rights of the suspect, the content and nature of detective services was carried out, which allowed to reveal the essence of private detective activity, its focus on protecting the constitutional rights of citizens, access to justice, assistance to law enforcement agencies in the fight against crime. The problems of the current legislation in the field of private detective activity are considered and ways of their solution are proposed. The necessity of adopting a law on private detective activity is substantiated. As a result of the study, the system of theoretical provisions, approaches to adequate provision in the Criminal Procedure Code of the Republic of Kazakhstan for the protection of citizens who have fallen into the sphere of criminal proceedings from encroachments on their legitimate rights and freedoms by the bodies of inquiry, investigation, prosecutor's office, etc., the importance and role of private detective activity, acting as a guarantee of the rights and freedoms of the suspect, are also substantiated in criminal proceedings.In the study of the questions posed, a logical, formal – legal, analytical, as well as functional method is used, revealing the qualitative characteristics of the subject of research, allowing to determine the essence of the institution under study, the possibility of regulatory impact of constitutional and sectoral legislation on the state of law and order in the Republic of Kazakhstan. In the scientific analysis undertaken by the authors, the principles of complexity and consistency are consistently implemented and productively combined, which made it possible to more fully, scientifically actualize the issues of improving criminal procedural capabilities for the realization of the rights and freedoms of a suspect during a pre–trial investigation.As a result of the study, it was found that the information collected by a private detective on a criminal case can be used by the pre-trial investigation bodies and the court in proving a criminal case, filing petitions, appealing actions and decisions of the preliminary investigation bodies and the court, which, in turn, would help individuals and legal entities to realize the constitutional right to access to justice.Keywords: criminal proceedings, participant in criminal proceedings, suspect, pre-trial investigation, private detective activity, guarantees.